A Study to Evaluate Risk of Ovarian Malignancy Algorithm (ROMA) in Patients with Ovarian Masses - Asna Aafreen; Aprajita Pankaj; Apoorv Pankaj (Asian Journal of Oncology, 2022)
Objective The aim of this study was to evaluate risk of ovarian malignancy algorithm (ROMA) in premenopausal patients with ovarian masses. Materials and Methods A mixed observational study was conducted in the Department of Obstetrics and Gynecology at Lilavati Hospital and Research Centre, Mumbai, from the month of June 2017 to March 2018. In this study, premenopausal females with ovarian masses, satisfying the inclusion criteria, were evaluated for the purpose of preoperative analysis. Results In premenopausal females, ROMA less than 11.4% is normal and more than or equal to 1.4% is increased. Considering histopathology reports as the gold standard, significant association was present between ROMA score and premenopausal status. Conclusion ROMA includes two recognized markers that are being used in the current scenario for the purpose of preoperative risk assessment of ovarian cancer, cancer antigen 125 (CA125), and human epididymis protein 4 (HE4). CA125 has been shown to be elevated in most ovarian cancer cells but has a low specificity for ovarian malignancies. HE4 is a recently developed biomarker that is elevated in ovarian cancers, as well as few other cancers, and has been shown to have higher specificity than CA125. Combining CA125 and HE4 provides a relatively more accurate prediction of malignancy than either test alone. ROMA culminates the benefits of the combined CA125 and HE4 biomarkers along with menopausal status to help assign a numeric risk stratification of malignancy in cases of ovarian tumors.